2012
DOI: 10.1186/1476-511x-11-117
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of dietary-fat induced blood–brain barrier dysfunction by anti-inflammatory lipid-modulating agents

Abstract: BackgroundSeveral studies have identified use of non-steroidal-anti-inflammatory drugs and statins for prevention of dementia, but their efficacy in slowing progression is not well understood. Cerebrovascular disturbances are common pathological feature of Alzheimer’s disease. We previously reported chronic ingestion of saturated fatty acids (SFA) compromises blood–brain barrier (BBB) integrity resulting in cerebral extravasation of plasma proteins and inflammation. However, the SFA-induced parenchymal accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 55 publications
2
31
0
1
Order By: Relevance
“…Similarly, in the meta-analysis of the discovery and replication sets, evidence of the involvement of rs10198175 in risk for BD and BE was strengthened in both the case-only and subtype analyses. APOB is a protein-coding gene for apolipoprotein B, the main component of chylomicrons and low density lipoproteins (LDL), implicated in the pathogenesis of atherosclerosis (Park et al, 2011), cardiovascular disease (Willer et al, 2008), cerebral β-amyloidosis, cognitive decline (Ramirez et al, 2011) and blood–brain barrier disruption (Pallebage-Gamarallage et al, 2012). Individual reports have implicated APOB mutations with suicide and violent behavior (Ramirez et al, 2011); on the other hand, mixed evidence has emerged, regarding a possible role in the interaction between depressive symptoms and atherogenic metabolic profiles (Hummel et al, 2011); yet its brain functional role is not completely understood (Elliott et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the meta-analysis of the discovery and replication sets, evidence of the involvement of rs10198175 in risk for BD and BE was strengthened in both the case-only and subtype analyses. APOB is a protein-coding gene for apolipoprotein B, the main component of chylomicrons and low density lipoproteins (LDL), implicated in the pathogenesis of atherosclerosis (Park et al, 2011), cardiovascular disease (Willer et al, 2008), cerebral β-amyloidosis, cognitive decline (Ramirez et al, 2011) and blood–brain barrier disruption (Pallebage-Gamarallage et al, 2012). Individual reports have implicated APOB mutations with suicide and violent behavior (Ramirez et al, 2011); on the other hand, mixed evidence has emerged, regarding a possible role in the interaction between depressive symptoms and atherogenic metabolic profiles (Hummel et al, 2011); yet its brain functional role is not completely understood (Elliott et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This might happen after chronic ingestion of dietary fat with a high content of saturated fatty acids. 37 In addition, PUFA, such as arachidonic acid, can enhance oxidative stress in endothelial cells and, thereby initiate the dysfunction of the BBB. 38 …”
Section: Blood-brain Barrier Permeability and Uptake Of Fatty Acidsmentioning
confidence: 99%
“…In line with the latter, an in vitro study using human cerebral microvascular endothelial cells showed that simvastatin and lovastatin attenuated Aβ-induced BBB dysfunction [85]. Moreover, in a mouse model of dietary- induced BBB dysfunction, we demonstrated that atorvastatin and pravastatin reversed the disruption of BBB integrity [86]. Interestingly, all studies indicated here reported the BBB protective effects of statins independent of their lipid-lowering effects but rather occurred concomitant with attenuated oxidative stress, suggesting its cerebrovascular protective action through anti-oxidative pathways.…”
Section: Antioxidants Cognitive Decline and Blood-brain Barriermentioning
confidence: 64%